Mapping the Research Landscape in Malaysia: A Bibliometric Analysis of Early Childhood Education and Development Publications - Cheah, Ee Lynn; Kong, Kimberly (Southeast Asia Early Childhood Journal, 2024)
This study presents a comprehensive bibliometric analysis of early childhood education and development research in Malaysia, focusing on articles published in Scopus. Publications included in this study consisted of journal articles, books and book chapters, and conference papers, all of which sampled children between four to seven years old. The resulting publications were cleaned up in Open Refine, then later loaded into Excel and Harzing’s Publish or Perish for analysis. Visualisations were generated using VOSViewer. The aim was to investigate the publication patterns, citation trends, and collaboration networks of researchers in this field. A total of 250 publications from 1988 to 2022 were analyzed, with a significant increase in publication output observed in the last five years (2017-2022). The results revealed 1576 citations, an average of 46.35 citations per year, and 6.30 citations per paper. The h-index and g-index were found to be 21 and 29, respectively, indicating a growing impact of Malaysian early childhood research in the global academic community. Annual collaboration metrics revealed a diverse range of collaborative efforts among researchers, with the Degree of Collaboration and Collaborative Coefficient showing varying degrees of research partnerships. The collaboration network visualization indicated 31 clusters and 95 items, with the largest cluster containing 11 items, highlighting the potential for further interdisciplinary collaborations in the field. Despite the limitations of using a single database (Scopus) and focusing on a specific topic within the Malaysian context, this bibliometric analysis provides valuable insights into the research landscape of early childhood education and development in Malaysia. Future studies could expand the scope to include additional databases, as well as explore emerging research trends and potential areas for collaboration. This study serves as a foundation for understanding the research dynamics in the field, which could help guide future research endeavours and inform policy and practice in early childhood education in Malaysia.